Technical and Vocational Education: Challenges Towards Youths Empowerment in Kano State-Nigeria - Idris, Ali; Mbudai, & Yohanna (Journal of Technical Education and Training, 2017)
Technical and Vocational Education System in Nigeria is designed to produce competent craftsmen for different sector of the economy who are expected to secure employment, become self-employed as well as employ others after graduation. Though, so many models were employed towards the development of work-related knowledge, attitudes and skills, however, the development of skills for the training of such personnel have not been successful in recent years. The research was conducted using qualitative method with ten participants interviewed (five principals and five heads of department) of technical colleges in Kano State. Content analysis technique was employed in the analysis of data collected from the interviews. The result obtained from the study shows that, the curriculum of Technical And Vocational Education is adequate in terms of content and also covers the skill element needed but it is lacking in terms of implementation towards achieving the desired national goals. The curriculum favors technical colleges to be operated as training institution for the graduates to further their education but not for employment as designed by the policy because of the fewer number of practical periods allocated for the trade subjects. The study recommends for the provision of adequate training facilities as well as training and re-training of teachers for effective skills development for employment.